2022
DOI: 10.1021/acs.joc.1c02753
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies toward 1,2,3,3a,4,8b-Hexahydropyrrolo[3,2-b]indole Core. Unusual Fragmentation with 1,2-Aryl Shift

Abstract: Base-assisted transformations of 2-(3-oxoindolin-2-yl)­acetonitriles were investigated. Unexpectedly, attempted reactions of substrates possessing nonprotected nitrogen atoms were accompanied by unusual extrusions of 2-arylacetonitriles, followed by a 1,2-aryl shift to afford 3-hydroxyindolin-2-ones. On the other hand, the reactions for N-alkyl derivatives of oxoindolines took the expected route by only providing 1,2,3,3a,4,8b-hexahydropyrrolo­[3,2-b]­indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Also, under the given conditions, the reaction of the N -unsubstituted indolinone 2a-H with both MeONa and NaH resulted in degradation products rather than the corresponding 3-hydroxyindolin-2-one 12 . And similarly, to our previous observation, 55 the yield of 3a has decreased upon lowering of the amount of base to 2 equivalents (entries 4, 5).…”
Section: Table 1 Search For a Base To Promote Indolinon...supporting
confidence: 90%
See 2 more Smart Citations
“…Also, under the given conditions, the reaction of the N -unsubstituted indolinone 2a-H with both MeONa and NaH resulted in degradation products rather than the corresponding 3-hydroxyindolin-2-one 12 . And similarly, to our previous observation, 55 the yield of 3a has decreased upon lowering of the amount of base to 2 equivalents (entries 4, 5).…”
Section: Table 1 Search For a Base To Promote Indolinon...supporting
confidence: 90%
“…Meanwhile, our initial studies have shown 55 that the treatment of oxoindolyl acetonitriles 2 with 6 equivalents of potassium hydroxide (KOH) in refluxing ethanol (EtOH) gives, unexpectedly, pyrroloindolinones 11 for N -alkyl starting material 2 (Scheme 4d ) and 3-hydroxyindolin-2-ones 12 together with the ejected R 2 CH 2 CN cyanide molecule in the case of N -unsubstituted precursors 2 (Scheme 4e ).…”
Section: Table 1 Search For a Base To Promote Indolinon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we proposed a plausible base-assisted mechanism formation of 3-hydroxyindolin-2-one 9 from 2-(3-oxoindolin-2-yl)-2-arylacetonitriles 6 [ 23 ]. The extrusion of phenylacetonitrile molecule gives the intermediate 3 H -indol-3-one 2 which, in turn, upon nucleophilic attack of hydroxide ion across C=N bond of the corresponding cyclic imine provides 3-oxoindolin-2-olate species 7 ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, we recently demonstrated that nitroolefins might act as 1,4-CCNO dipoles in reaction with indoles in the presence of phosphorous acid; this unusual transformation efficiently leads to the formation of stereo-defined spirocyclic scaffolds 5 , which are versatile and affordable synthetic equivalents of highly functionalized indoles [ 19 , 20 ]; it was shown that upon treatment with mild acids or bases as well as under neutral condition upon heating ( Scheme 1 ) spiranes 5 could be diastereoselectively transformed into 2-(3-oxoindolin-2-yl)-2-arylacetonitriles 6 [ 21 , 22 ]. Further extrusion of 2-phenylacetonitrile molecule followed by the formation of postulated intermediate 2 was used by us to design cascade sequence involving 1,2-aryl shift and leading to 3-hydroxyindolin-2-ones 9 ( Scheme 2 ) [ 23 ]. At some point, we speculated that such in-situ generated 3 H -indol-3-one 2 in the presence of 1,2-diaminoarenes 3 could provide an alternative redox-neutral method for the preparation of quinoxalines 4 ( Scheme 1 ) and below is our report on the development of this idea.…”
Section: Introductionmentioning
confidence: 99%